The Bottom-Up Approach. Experiences with the Impact Assessment of EU and National Legislation in the German, Dutch and Belgian Cross-Border Regions - Unfried, Martin; Kortese, Lavinia Susan Josephine; Bollen-Vandenboorn, Anouk (Territorial Impact Assessment, 2020)
Aus den Verlagsangaben: „Considering the myriad cross-border regions that the EU counts, it is impossible for the European Commission to map detailed territorial cross-border effects in all of the EU’s border regions for the impact assessments it conducts. National governments also face obstacles when seeking to cohesively integrate cross-border impact assessments in the existing frameworks that they use to assess the impact of new legislative, policy and enforcement measures. Even border regions or cross-border entities themselves face challenges in implementing impact assessments in their own territories. Despite the need for structural analyses of the border effects of newly adopted legislation and legislation under review, in terms of policy and enforcement, there are issues regarding the availability of academic resources, relevant tools and know-how. For the last couple of years, researchers from Maastricht University have been assessing as a bottom up exercise the potential effects of legislative proposals on the specific Dutch/German and Dutch/Belgium cross-border territories. This article presents the methodology used and the experiences gained from 2016 to 2019 by highlighting a number of interesting cases. It also offers future ideas for conducting similar “bottom-up” regulatory territorial impact assessments in cross-border regions.“
Keywords: Euregio Maas-Rhein; Gesetzgebung; Grenzgebiet; Wirtschaftsbeziehungen; Wirtschaftsentwicklung

„Die geographische Lage hat uns zu Nachbarn gemacht. Eine stetige Zusammenarbeit hat uns zu Partnern gemacht.“ Die deutsch-belgischen Wirtschaftsbeziehungen seit 1945 und die Schlüsselrolle einer Grenzregion - Quadflieg, Peter M. (Geschichte im Westen, 2015)
Keywords: Ostbelgien; Wirtschaftsbeziehungen; deutsch-belgische Beziehungen

„Invoer te lande verboden“. Een verkenning van de handel over landwegen tussen Nederland en de Pruisische provincies Rheinland en Westfalen, 1836–1857 - Lewe, Agnes (N. W. Posthumus reeks, 1995)
Keywords: Handel; Preußen; Rheinland; Westfalen; Wirtschaftsbeziehungen

De Oostgelderse textielindustrie en de grens - Beukelaer, Hans de (Grenzen komen en gaan, kommen und gehen, 1993)
Keywords: Aalten; Bocholt; Provinz Geldern; Textilindustrie; Wirtschaftsbeziehungen

Städtedreieck Enschede/Hengelo – Münster – Osnabrück. Rahmenbedingungen, Entwicklungschancen, Gestaltungsmöglichkeiten – Kurzbericht über ein Forschungsprojekt - Michels, Winfried (Zentrum für Niederlande-Studien, Jahrbuch, 1992)
Keywords: Enschede; Grenzüberschreitende Kooperation; Grenzüberschreitende Regionalplanung; Hengelo; Infrastruktur; Münster (Westf); Osnabrück; Raumordnung; Verkehrsplanung; Wirtschaftsbeziehungen

De lakenfabriek Scheibler, Ronstorff, Rahlenbeck te Dalem (1774–1890). Een voorbeeld van industrialisatie op het platteland - Leboutte, René (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 1979)
„R. Leboutte, medewerker van het Musée de Fer et de l'Acier te Luik, geeft een overzicht van de geschiedenis van een middelgroot textielbedrijf te Dalem. Deze studie is daarom zo belangrijk, omdat Dalem een der hoofdplaatsen van de landen van Overmaze is geweest en tot aan het laatste kwart van de 18e eeuw onder Noord-Nederlands bestuur heeft gestaan. Desondanks is aan de historie van deze stad in de Nederlands-Limburgse historiografie nooit veel aandacht besteed. Hoewel dit verzuim door het hier gepubliceerde artikel uiteraard niet geheel wordt goedgemaakt, is het toch verheugend dat aan de hand van het gebeuren in Dalem de samenhang tussen de bedrijvigheid in Eifel, Ardennen en Zuid-Limburg kan worden verduidelijkt. De stichters van de hier bestudeerde onderneming, de familie Scheibler, had destijds industriële belangen in Monschau, Eupen, Eijsden en Dalem, een gebied dat eens samenhang vertoonde en thans door de 19e eeuwse grensafbakening in drie staten terecht gekomen is.“
Keywords: Dalhem; Eijsden; Eupen; Ländlicher Raum; Monschau; Textilindustrie; Wirtschaftsbeziehungen

Zur Geschichte der Textilindustrie im Euregio-Gebiet - Schweizer, Wilhelm F. (Stichting Textielgeschiedenis, 1976)
Keywords: Münsterland (West); Textilindustrie; Twente; Wirtschaftsbeziehungen

Die Berkelschiffahrt in der Wirtschaftsgeschichte des niederländisch-westfälischen Grenzraumes - Terhalle, Hermann (Beiträge des Heimatvereins Vreden zur Landes- und Volkskunde, 1975)
Keywords: Berkel (Fluss); Binnenschifffahrt; Fluss; Handel; Infrastruktur; Münsterland (West); Niederlande (Ost); Wirtschaftsbeziehungen

Die Textilindustrie des deutsch-niederländischen Grenzgebietes in ihrer wirtschaftsgeographischen Verflechtung - Kötter, Heinrich (Arbeiten zur rheinischen Landeskunde, 1952)
Abstract: „Die vorliegende Arbeit will versuchen, einen Überblick über die wirtschaftsgeographische Verflechtung der Textilindustrie des deutsch-niederländischen Grenzgebietes zu geben. Diese Verflechtungen bestehen sowohl zwischen den einzelnen Produktionszweigen der jeweiligen Gebiete, als auch zwischen dem deutschen und dem niederländischen Teil des Grenzgebietes. Die Wurzeln dieser Verflechtung reichen zum Teil sehr tief und mußten bis zu ihrem Ursprung hin verfolgt werden.“
Keywords: Hochschulschrift; Münsterland (West); Niederlande (Ost); Textilindustrie; Twente; Wirtschaftsbeziehungen